Pengaruh Service Quality in Glamping dan Sustainable Glamping Experiencescape Terhadap Behavioral Intention - Juliana Dian Astari; Oce Ridwanudin; Yeni Yuniawati (MAMEN: Jurnal Manajemen, 2026)
The growth of the glamping industry has prompted destination managers to improve service quality and create sustainable lodging experiencescape to meet tourists’ needs and expectations. This study aims to analyze the influence of glamping service quality and the sustainable glamping experiencescape on tourists’ behavioral intentions at Bobocabin Cikole. This study employs a quantitative method with a explanatory approach. Data were collected through an online questionnaire distributed to 373 respondents who had previously stayed at Bobocabin Cikole. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software. The results indicate that the research model exhibits a good level of goodness of fit. Partially, glamping service quality has a positive and significant effect on tourists’ behavioral intentions. Meanwhile, the sustainable glamping experiencescape does not have a significant direct effect on tourists’ behavioral intentions. These findings indicate that improving service quality is a key factor in driving tourists’ behavioral intentions, such as the desire to revisit, recommend the destination to others, and post positive reviews. Therefore, glamping operators need to continuously improve service quality to maintain competitiveness and enhance tourist satisfaction.